Loyalitas Pegawai Di Lingkungan Kerja Pemerintahan Dinas Pemuda Dan Olahraga Jawa Barat - Muhamad Alamsyah Nasution; Ageng Saepudin Kanda (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Dispora or Youth and Sports Service is a regional government located in the province or district/city. Dispora has an important role in developing youth potential and advancing the field of sports in a country or certain city district, and its objectives include developing leadership, creativity and youth skills. , as well as increasing achievement and participation in sports activities to support overall Community Health and Development. The general aim of this research is to find out what influences employee/worker loyalty in completing performance programs that will be implemented in the Youth and Sports Department. This research uses a research method with a qualitative approach, where the research carried out is descriptive. The focus of this research is the achievement of work results (performance) of government officials at the Youth and Sports Department in increasing loyalty to performance by analyzing problems, especially regarding employee readiness and response to performance and loyalty. The results of this research are that employee loyalty is one of the keys to the success of a program. performance, so as to reduce the risk of failure in the performance program, suggestions: To increase employee morale and work motivation, leaders should act more wisely, so that appropriate work programs are created.